A concise history of Mexico - Hamnett, Brian R. (Cambridge concise histories., 1999)
"Mexico's fascinating complexities are difficult to approach. This illustrated Concise History begins with a brief examination of contemporary issues, while the book as a whole - ranging from the Olmecs to the present day - combines a chronological and thematic approach while highlighting long-term issues and controversies over interpretation." "The book's prime objective is accessibility to a range of readers, including those interested in gaining a broad general knowledge of the country and those across the professions anxious to acquire a rapid but secure understanding of a subject where there are few starting points."--Jacket.